Menilai Audit Firm Rotation, Gender Komite Audit, Struktur Kepemilikan, Audit Fee Dan Kualitas Audit – Studi Kasus Pada Industri Perbankan Indonesia - Efva Octavina Donata Gozali; Ruth Samantha Hamzah; Anisa Listya (Politeknik Ganesha Medan, 2023)
Poor audit quality has become the noteworthy issue in recent years, particularly in developing countries such as Indonesia. This study therefore aims to bridge the information and audit quality gap in Indonesia banking industries by examining the relationship between audit firm rotation, audit committee gender, and ownership structure on audit quality. Quantitative approach by employing logistic regression was used as the analysis method. The sample in this study was banking companies listed in Indonesia Stock Exchange which obtained 80 year-observation samples in the period of 2011-2020. The results of this study indicate that audit fees have a significant effect on audit quality. Meanwhile, audit firm rotation, audit committee gender, and ownership structure which are proxied by institutional ownership, managerial ownership, government ownership have no significant effect on audit quality.